PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL PADA MATA PELAJARAN IPAS MATERI WARISAN BUDAYA INDONESIA YANG MENDUNIA SISWA KELAS VI SD - Ni Luh Sinta Noviani; L. Heny Nirmayani; Putu Eka Sastrika Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This development research aimed to produce a digital comic learning media suitable for teaching the Indonesian Natural and Social Sciences (IPAS) subject on the topic Indonesian Cultural Heritage Recognized Worldwide for sixth-grade elementary school students and to evaluate its validity and practicality. The study employed the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation), although the research was conducted only up to the implementation stage. The study was carried out in Cluster VI Elementary Schools, Sawan District, involving three expert validators (content, media, and language experts), two sixth-grade teachers, and 20 sixth-grade students. Data were collected through questionnaires and analyzed using descriptive quantitative and qualitative techniques. The developed product was a digital comic created using Canva with Artificial Intelligence support and published as a digital flipbook through Heyzine. The learning media presents instructional content in several episodes and is enriched with interactive features, audio narration, cultural information buttons, learning summaries, and evaluation quizzes. The validity assessment yielded an Aiken's V index of 0.90, indicating a very high level of validity based on evaluations by the content, media, and language experts. The practicality test showed average scores of 92% from teachers and 90% from students, both categorized as very practical. These findings indicate that the developed digital comic learning media meets the criteria of validity and practicality and is therefore suitable for use as an alternative IPAS learning medium to promote more engaging, interactive, and meaningful learning experiences for sixth-grade elementary school students.